2017
DOI: 10.1007/978-3-319-70833-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Robot Localization System in a Hard Outdoor Environment

Abstract: Localization and mapping of autonomous robots in a hard and unstable environment (Steep Slope Vineyards) is a challenging research topic. Typically, the commonly used dead reckoning systems can fail due to the harsh conditions of the terrain and the Global Position System (GPS) accuracy can be considerably noisy or not always available. One solution is to use wireless sensors in a network as landmarks. This paper evaluates a ultra-wideband time-of-flight based technology (Pozyx), which can be used as cost-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Model based temperature compensation for the bias in Inertial Measurement Units (IMUs) has been implemented in systems such as those used by the Pixhawk flight controller; however, empirical studies of the sensor measurement variance are lacking for cases of deployed sensors. Previous investigations have shown that the generalised variance of the system exhibits a correlation between the range of the anchor node and the ranging node; this is corroborated by work completed by [9].…”
Section: Model-based Sensor Measurement Variancesupporting
confidence: 53%
See 4 more Smart Citations
“…Model based temperature compensation for the bias in Inertial Measurement Units (IMUs) has been implemented in systems such as those used by the Pixhawk flight controller; however, empirical studies of the sensor measurement variance are lacking for cases of deployed sensors. Previous investigations have shown that the generalised variance of the system exhibits a correlation between the range of the anchor node and the ranging node; this is corroborated by work completed by [9].…”
Section: Model-based Sensor Measurement Variancesupporting
confidence: 53%
“…The Pozyx is a low cost UWB sensor network which deploys the Time of Flight (TOF) range measurement technique, where a mobile tag receives range measurements from anchors with known locations scattered in an environment [15]. Localisation from the Pozyx is accomplished through a lateration (three anchors) or multi-lateration (>3 anchors) process which is solved using a linear least squares (LLS) implementation [9].…”
Section: Ultra Wide-band Positioningmentioning
confidence: 99%
See 3 more Smart Citations